Methodologies for ex-ante evaluation of the economic benefits of biotechnology in potato cultivation in Peru - de los Reyes Maza y Silupú, Santos (2023)
Agricultural technologies must be evaluated before their implementation so that decision makers have objective elements to support their judgment. Given the differences in the results if deterministic or probabilistic methods of ex-ante evaluation of technologies are used, the aim is to determine which are more efficient in the ex-ante evaluation of genetically modified potato seeds resistant to blight or late blight (caused by Phytophthora infestans) and potato tuber moth (Phthorimaea operculella). Resistance to these biotic agents is achieved with genes from wild potatoes (cisgenic modification) that provide resistance to late blight and with genes from Bacillus thuringiensis (transgenic modification) that provide resistance to potato tuber moth. The objective was to compare the deterministic and probabilistic versions of the partial budget and surplus-change methods, applying them to the case of evaluating the economic effects of releasing genetically modified potato seeds resistant to blight and moth. Greater efficiency of probabilistic methodologies is verified, because they show positive and negative probabilities of the benefits of the technology, giving a realistic image of its expected success, surpassing deterministic methods that only find positive and unique values. Consequently, it is recommended to apply probabilistic methods for their usefulness in government decision making, by showing ranges of success and failure.